RETORIKA SEBAGAI ILMU KOMUNIKASI DALAM BERDAKWAH - Asriadi Asriadi (Institut Agama Islam Negeri Kendari, 2020)
Rhetoric is a game, processing or language style that we use in delivering a message in the form of speeches, lectures and others to mad`u. Speaking or giving speeches in public places there are several things that must be noticed by the communicant in order to know, so that they must be able and able to master the